2019
DOI: 10.1177/0950017019882904
|View full text |Cite
|
Sign up to set email alerts
|

Healing or Deepening the Scars of Unemployment? The Impact of Activation Policies on Unemployed Workers

Abstract: Unemployment has severe consequences that persist over the life course, including higher risk of future unemployment and worse employment conditions. While the existence of scarring effects has become conventional wisdom, labour market sociologists have pointed out that their magnitude differs between institutional contexts. Recently, the focus of the discussion has shifted towards the role of activation policies, which are suspected to speed up labour market integration but worsen reemployment quality, hereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Previous research on the activation period has confirmed that it indeed fosters exit into employment, which means that it successfully filters out individuals who could find a job in a relatively short period of time using increased activation and monitoring measures only. In total, about 10% of participants at the activation period have found employment before the end of the activation period, which is 2.5% points higher than the matched control group (IAW and ISG 2015;Fervers 2019).…”
Section: Structure Of the Programmementioning
confidence: 83%
See 1 more Smart Citation
“…Previous research on the activation period has confirmed that it indeed fosters exit into employment, which means that it successfully filters out individuals who could find a job in a relatively short period of time using increased activation and monitoring measures only. In total, about 10% of participants at the activation period have found employment before the end of the activation period, which is 2.5% points higher than the matched control group (IAW and ISG 2015;Fervers 2019).…”
Section: Structure Of the Programmementioning
confidence: 83%
“…Overall, the descriptives reinforce that the group of unemployed job seekers are characterized by rather low labour market attachment. This results from the pre-selection due to the activation period as well as the selection into the activation period, as individuals with rather unfavourable characteristics have participated here (see Fervers 2019).…”
Section: Data and Variablesmentioning
confidence: 99%
“…As an antidote, intensive contact between advisers and unemployed individuals can enable precise knowledge of the latter's individual strengths and weaknesses. Furthermore, evidence suggests that intensifying contact between advisers and such individuals positively affects their transition into gainful employment (Fervers, 2019; Rosholm, 2014). Nevertheless, as the cases also imply, close contact should be made optional, for some individuals need close assistance, whereas others flourish best by being freed from the pressure of formal regulations.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, outstanding economic development since 2010 and the accompanying drop in unemployment readily create the impression that Germany's unemployed should be easy to activate. Moreover, the dual trends suggest that if activating the unemployed fails, then the lack of labour market integration can be attributed primarily to individual instead of institutional deficiencies, thereby perpetuating the counterfactual perception that long‐term unemployment stems from individual failure and/or unwillingness to work (Fervers, 2019; McKay, 2014). However, the German Federal Employment Agency (Bundesagentur für Arbeit, 2010) cannot create jobs on the primary labour market but only redistribute labour market opportunities.…”
Section: Germany's Employment Agency As a Redistributor Of Opportunities In Light Of European Labour Market Policiesmentioning
confidence: 99%
“…This builds on McCollum’s (2012) explicit contention that greater employer participation in ALMPs can enable a ‘win-win-win’ situation in which jobseekers are matched to and given appropriate training for existing vacancies, employers get employees that are work-ready and supported in work, and service providers get their clients into jobs. Greer’s (2016) call for more research into resistance against ALMPs by claimants and workers goes unheeded and recent contributions to debate continue on largely well-trodden themes such as ‘what works’ (Adam et al, 2017), whether ALMPs are successful in reaching disadvantaged groups (Bonoli and Liechti, 2018), comparisons of different approaches to ALMPs (Froyland et al, 2018) and the impact of ALMPs on unemployed people (Fervers, 2019).…”
Section: Introductionmentioning
confidence: 99%